Correlation Between Red Meat and Offal Consumption and Total Blood Cholesterol Levels Among Administrative Staff at Universitas YARSI and its Review from Islamic Perspective - Aulia Nadira Prasetya; Sri Utami; Endah Purnamasari; Andri Gunawan (Universitas Ibn Khaldun Bogor, 2026)
High total cholesterol levels are a major risk factor for cardiovascular disease. Consumption of red meat and offal, which are high in saturated fat and cholesterol, can increase total blood cholesterol levels. Dietary patterns in urban communities, including academic staff, show a tendency toward increased consumption of high-fat animal products. From an Islamic perspective, adhering to a halal and thayyib diet and avoiding excess are essential principles in maintaining health, including regulating the intake of red meat and offal. This research used a quantitative method with a prospective cohort design involving 14 days of consumption recording using an estimated food record among 38 male respondents aged < 60 years. Total cholesterol examinations were conducted before and after the study using the enzymatic method with the Mindray BS series chemistry analyzer. Normality tests were performed using Shapiro–Wilk and Kolmogorov–Smirnov. The correlation between red meat consumption and total cholesterol was analyzed using Pearson’s correlation test, while offal consumption was analyzed using Spearman’s correlation test. The study results indicated a significant positive relationship between red meat consumption and changes in total cholesterol levels (r = 0,385; p = 0,017). Offal consumption also showed a significant positive relationship with changes in total cholesterol levels (rₛ = 0,419; p = 0,009). Most respondents experienced a decrease in total cholesterol levels after the study, although higher consumption of red meat and offal remained associated with increases in cholesterol levels. There is a significant relationship between the consumption of red meat and offal and total blood cholesterol levels. The higher the consumption of both, the greater the increase in total cholesterol. These findings align with Islamic principles emphasizing the importance of consuming food that is halal, thayyib, and not excessive in order to maintain physical health.